2004
DOI: 10.1080/1034912042000182210
|View full text |Cite
|
Sign up to set email alerts
|

Literacy skills of adults with intellectual disabilities in two community‐based day programs

Abstract: There is limited information available related to the literacy skills of adults with intellectual disabilities. In this project, information was collected about the contexts, current practices, and clients' abilities in literacy in two community-based disability service programs. Individual assessments were undertaken to collect details of the current literacy levels of adults with intellectual disabilities in day program settings. These assessments focused on receptive language, reading at the letter, word an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…The client data suggested that the adults with intellectual disabilities who volunteered to participate in the project, had a range of literacy skills, were interested in pursuing literacy related activities that were connected to their lives, for example, reading magazines, and writing about their experiences (for a more detailed report of these data see Young et al 2004). …”
Section: Participantsmentioning
confidence: 98%
See 2 more Smart Citations
“…The client data suggested that the adults with intellectual disabilities who volunteered to participate in the project, had a range of literacy skills, were interested in pursuing literacy related activities that were connected to their lives, for example, reading magazines, and writing about their experiences (for a more detailed report of these data see Young et al 2004). …”
Section: Participantsmentioning
confidence: 98%
“…With this narrow approach to training, some adult services have developed functional literacy by focusing on reading and writing for tasks such as employment, cooking, banking and travel (van Kraayenoord 1992, Hendrick et al 1999, Young et al 2004. However, first, the effectiveness of such programs was hampered by the limited knowledge and training of disability support staff who needed to further develop their understandings of literacy, and to learn how to understand and develop the capabilities of individuals with intellectual disability more effectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This definition was based on evidence that suggests that some recruitment and data collection methods cannot be relied on due to challenges with low literacy. 17 Identification of people with intellectual disability Across these 11 journals, we reviewed articles published from January 2010 to December 2011; each journal was searched using the terms 'intellectual disability', 'learning disability', 'learning difficulties', 'mental retardation' and 'developmental disability'. As the aim of this part of the study was to determine how people with intellectual disability are identified in mainstream public health research, studies specific to this population were excluded.…”
Section: Inclusion Of People With Intellectual Disabilitymentioning
confidence: 99%
“…In addition, research by the Latch-On team (Moni and Jobling, 2002) and others (Young, Moni, Jobling and van Kraayenoord, 2004) has shown that learners with intellectual disabilities including Down syndrome have a diverse range of literacy abilities and computer skills. One size does not fit all.…”
Section: The Latch-on™programmentioning
confidence: 99%